A cross-sectional survey of the acceptability of data collection processes for validation of a European point prevalence survey of healthcare-associated infections and antimicrobial use. Issue 3 (May 2016) - Price, Lesley; Reilly, Jacqui; Godwin, Jon; Cairns, Shona; Hopkins, Susan; Cookson, Barry; Malcolm, William; Hughes, Gareth; Lyytikäinen, Outi; Coignard, Bruno; Hansen, Sonja
Background: Statistical measurements alone are insufficient to ensure robust data for point prevalence surveys (PPS) of healthcare-associated infections (HAI). Data quality is determined by the type of data, data collection methods and available resources. Data collectors' views regarding the acceptability of data collection process for validation studies are also important to consider. Aim: To explore data collectors' views on the acceptability of data collection processes used for a European validation PPS of HAI and antimicrobial use (AMU). Methods: An anonymous online survey was conducted with 67 data collectors from 10 European countries involved in the study. Findings: Twenty-five (64.1%) participants viewed AMU data collection as easy/quite easy whereas only five (12.8%) thought HAI data collection was easy/quite easy. Six (17%) participants indicated that incentives and 21 (56.8%) that disincentives were possibly/definitely present for reporting cases of HAI. Engagement of staff was not thought to have adversely affected data collection as only one (2.6%) and five (15.4%) participants thought involvement of hospital PPS teams and administration was low/very low, respectively. Discussion: Participants believed the approaches used were appropriate but that more training was required prior to data collection, some case definitions should be reviewed and the number of variables reduced.